STUDI KUASI-EKSPERIMENTAL: PENGEMBANGAN PROFESIONAL BERBASIS PENGALAMAN SEBAGAI IMPLEMENTASI PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR - Tika Puspita Widya Rini; Ali Rachman; Arta Mulya Budi Harsono; Aldy Ferdiyansyah; Ari Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of the Pancasila Student Profile Strengthening Project (P5) at the elementary school level was hampered by the gap between abstract curriculum policies and concrete pedagogical implementation. This study was look for the effectiveness of an experiential professional development model designed to address this gap. Using a single-group pretest-posttest quasi-experimental design (N=30 teachers), the intervention utilized the Beeswax and Tomato Flower Utilization project in wetland-based cosmetic development as a pedagogical blueprint for realizing the P5 dimensions. The results showed a statistically significant increase in teacher competency (p<.001), with an N-gain score reaching 0.70, classified as High. This intervention significantly changed the competency landscape: from 54% of teachers previously at the Fair to Poor understanding level, 100% achieved Good to Very Good levels after the training, with 77% in the highest category. This cognitive leap was driven by remarkable emotional engagement (100% concentration, 63% active participation). This study provides compelling evidence that transforming abstract curriculum concepts into concrete, real-world experiences is an effective method for teacher professional development, providing a measurable and repeatable framework for addressing the challenges of implementing P5 at the national level.